Leap Motion para interfaces baseadas em WIMP - Manuel César Bessa Seixas (2014)
The dissertation "Leap Motion for WIMP based interfaces " aims to perform an evaluation on the Leap Motion device, namely when used to interact with WIMP interfaces. The Leap Motion is a relatively recent device that has been causing some impact in the market due to the way the interaction with the computer is performed. The device is able to detect the position, inclination and orientation of the human palm and fingers of both hands (it's also able to detect objects) and use their movements and gestures to control the computer. The device throughput (performance) and precision were evaluated when used to interact with the WIMP interfaces ( Windows, Icons, Menus, Pointers). This way, it's possible to identify if this kind of device is adequate to this kind of interfaces and what measures/changes need to be taken in these, if necessary, to improve the Leap Motion performance, or vice-versa. To perform this evaluation the ISO 9241-9:2000 standard will be used, standard that will allow to evaluate any device performance as a pointing device. To complement this standard MacKenzie, Kauppinen e Silfverberg article ("Accuracy Measures for Evaluating Computer Pointing Devices") being this used to classify the movement/trajectory performed by the pointer. The task evaluated was "selection". This means, moving the pointer/cursor to a target and select it successfully. A commercial application, named Touchless, was also used to convert index finger position and movement to a pointer. In order to determine in where the Leap Motion is better or worse than the other devices, the same evaluation was also executed in other equipement, namely the computer mouse and the touchpad. Taking in account the attained results, the Leap Motion performance was lower than the remaining devices. In order to try to understand if this result was really due to the device and not due to the used gesture (Touchless application), the study was further complemented by carrying out the same evaluation using a new gesture.